Pedagogical Values in QS. Al-An’am Verse 32 and Implications on Life Goals: An Islamic Education Perspective - Amanda Resti Maulidiya; Sofyan Sauri (Yayasan pendidikan dzurriyatul Quran, 2025)
QS Al-An'am verse 32 emphasizes that the life of the world is only a game and entertainment, while the afterlife is the real life. This research aims to discuss the pedagogical values in QS. Al-An'am verse 32 and its implications for the purpose of human life from an Islamic perspective. Through a literature study approach, this research explores the views of the mufasirs. The results of this study reveal that QS. Al-An'am verse 32 provides important insights for a Muslim's view of life in navigating life in the world and preparing for life in the hereafter. This verse emphasizes that the world is only temporary and full of impermanent pleasures. Therefore, humans are invited to make the life of the world a means to achieve true happiness in the hereafter. The pedagogical values contained in this verse have important implications in Islamic education, namely forming a generation of faith, piety, and noble character. These values include; (1) fostering faith and piety as the main foundation of a Muslim's life, (2) teaching that the world is used as a tool to achieve happiness in the hereafter, not the ultimate goal, (3) awareness that everything you have is a mandate of Allah that must be accounted for, (4) the importance of gratitude and staying away from excessive love of the world. Education based on Qur'ani values like this is expected to create a generation that is not only intellectually intelligent, but also morally and spiritually strong, ready to face life's challenges with full responsibility and wisdom.